Violence and restraint in civil war : civilian targeting in the shadow of international law - Stanton, Jessica A. (London Cambridge Uni. Press, 2016)
"Media coverage of civil wars often focuses on the most gruesome atrocities and the most extreme conflicts, which might lead one to think that all civil wars involve massive violence against civilians. In truth, many governments and rebel groups exercise restraint in their fighting, largely avoiding violence against civilians in compliance with international law. Governments and rebel groups make strategic calculations about whether to target civilians by evaluating how domestic and international audiences are likely to respond to violence. Restraint is also a deliberate strategic choice: governments and rebel groups often avoid targeting civilians and abide by international legal standards to appeal to domestic and international audiences for diplomatic support. This book presents a wide range of evidence of the strategic use of violence and restraint, using original data on violence against civilians in civil wars from 1989 to 2010 as well as in-depth analyses of conflicts in Azerbaijan, El Salvador, Indonesia, Sudan, Turkey, and Uganda"--
Partially based on author's thesis (doctoral - Columbia University, 2009) under the title: Strategies of violence and restraint in civil war.
Keywords: Civilians in war; Civilians in war -- Case studies; Civil war -- Protection of civilians; Civil war -- Protection of civilians -- Case studies